2024
DOI: 10.1111/iwj.14541
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D and wound healing: Assessing skin barrier function and implications for chloasma treatment

Qiong Chen,
Lin Liu,
Yi Zhang

Abstract: Chloasma, which is distinguished by irregularities in the pigmentation of skin, poses substantial challenge in the field of dermatology. The regulatory influence of vitamin D on the functions of skin cells implies that it may have the capacity to effectively treat chloasma and promote wound healing. To assess the efficacy of vitamin D in chloasma treatment and its impact on the function of skin barrier during the process of wound healing. The research spanned from April 2022 to September 2023, in Shanghai, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…We observed that physiological concentrations of 1,25(OH) 2 D 3 stimulate keratinocyte proliferation, while higher doses inhibit growth. Recently, the Zhang laboratory conducted a clinical trial demonstrating the efficacy of topical vitamin D 3 in treating chloasma, a condition of hypermelanosis occurring during pregnancy, as well as in enhancing wound healing outcomes [28]. In another study, the Watsky laboratory found that both topical 1,25(OH) 2 D 3 and 24,25(OH) 2 D 3 accelerate corneal wound healing in mice [29].…”
Section: Skin As a Mediator Of The Synthesis Of Vitamin Dmentioning
confidence: 99%
“…We observed that physiological concentrations of 1,25(OH) 2 D 3 stimulate keratinocyte proliferation, while higher doses inhibit growth. Recently, the Zhang laboratory conducted a clinical trial demonstrating the efficacy of topical vitamin D 3 in treating chloasma, a condition of hypermelanosis occurring during pregnancy, as well as in enhancing wound healing outcomes [28]. In another study, the Watsky laboratory found that both topical 1,25(OH) 2 D 3 and 24,25(OH) 2 D 3 accelerate corneal wound healing in mice [29].…”
Section: Skin As a Mediator Of The Synthesis Of Vitamin Dmentioning
confidence: 99%